Solvent free one-pot multi-component synthesis of beta-azaarene substituted ketones via a Sn-catalyzed C(sp(3))-H functionalization of 2-alkylazaarenes - Chavan, Santosh S.; Pathan, Mohsinkhan Y.; Mulla, Shafeek A. R. (RSC Advances, 2015)
A tin-catalyzed solvent free one-pot multi-component cascade reaction strategy for the direct Michael addition/C(sp(3))-H functionalization of 2-alkylazaarenes with aldehydes and ketones via an aldol reaction has been developed. This is the first report and provides cost effective new access to potent biologically/medicinally important azaarene derivatives with high atom economy.